2020
DOI: 10.1371/journal.pone.0235694
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses’ communication experiences with patients and families in an intensive care unit: A qualitative study

Abstract: This study evaluated the communication experiences of critical care nurses while caring for patients in an intensive care unit setting. We have collected qualitative data from 16 critical care nurses working in the intensive care unit of a tertiary hospital in Seoul, Korea, through two focus-group discussions and four in-depth individual interviews. All interviews were recorded and transcribed verbatim, and data were analyzed using the Colaizzi's method. Three themes of nurses' communication experiences were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 30 publications
1
23
0
9
Order By: Relevance
“…It has been demonstrated that adequate training on communication skills could have a direct impact on the mental health of workers and especially against burnout syndrome [ 17 , 20 ]. It has also been observed that the impact of the communication skills of emergency professionals is correlated with the satisfaction perceived by the patients and family members [ 48 ] and that communication skills improve the self-efficiency in professional practice perceived by the nursing professionals themselves [ 49 , 50 ]. Aspects that could have influenced participants’ stress, such as, for example, having children or elderly people at home, did not appear in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that adequate training on communication skills could have a direct impact on the mental health of workers and especially against burnout syndrome [ 17 , 20 ]. It has also been observed that the impact of the communication skills of emergency professionals is correlated with the satisfaction perceived by the patients and family members [ 48 ] and that communication skills improve the self-efficiency in professional practice perceived by the nursing professionals themselves [ 49 , 50 ]. Aspects that could have influenced participants’ stress, such as, for example, having children or elderly people at home, did not appear in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses provide comprehensive care, which comprises physical, mental and emotional care (Lee & Choe, 2021 ). Specifically, communication is essential during the provision of patient care (Yoo et al, 2020 ). Frontline nurses must provide care to patients under different circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…It is specially use for communication between a physician and a nurse when there is a change in patient condition or between a nurse and nurse during patients shift to a new department or during shift change. It is a technique used to deliver quality patient care [7] .…”
Section: Introductionmentioning
confidence: 99%